Genetics of Cone Morphology of Black Spruce [Picea-mariana (Mill). B. S. P.] in Newfoundland Canada - Khalil, M.A.K. (JD Sauerlaender's Verlag, 1984)
The paper presents the results of a study conducted to determine the relative role of genotypic and environmental control over characters of cone morphology and seed weight in black spruce (Picea mariana (MILL.) B.S.P.) A three-stage cluster sampling scheme was adopted with the sampling stages of populations, trees within populations and cones within trees. Nine characters of cone morphology were measured on each cone and mean 1,000-seed weight was determined for each tree. Statistical analyses comprised (1) calculation of popula tion means and standard deviations for each character, (2) cone length-cone diameter correlations at the populations and tree levels, (3) hierarchical analyses of variance and (4) comparison of the cone length-cone diameter correlations with similar values obtained six years earlier. Genetic ana lyses consisted of (1) calculation of repeatibility with stand ard error and confidence limits for each character at the population level as estimates of heritability; and (2) multiple regression analysis for each character. The latter was con ducted using the stepwise zig-zag procedure with cone character as the dependent variable and 12 environmental factors together with their squares and first order inter actions as independent variables to identify the subset which contributes most to the variation in the character. Though the means and repeatabilities of all characters vary with populations, no geographic trends can be dis cerned. Repeatability values have been shown to be good estimates of heritability. All characters are under statisti cally significant genotypic as well as environmental con trol and the most important subset of the latter has been identified. Cone length, diameter, and oven dry weight as well as dimensions of the middle scale are under strong, and length and width of the base and tip scale, under weak genotypic control. The earlier indications of pleiotropic control over cone length and diameter is supported. Seed weight is under weak environmental control.